Parametric Study for Maximizing Heating Value Of Gasification Syngas - Atnaw, Samson M.; Shaharin, A. Sulaiman; Suzana, Yusup (2014)
The potential of oil palm derivative biomass for renewable energy in major producing countries in the South East Asia has been well documented involving a number of experimental and theoretical studies on energy conversion of this abundant biomass residue. In previous studies, results of equilibrium model of downdraft gasification of oil palm fronds (OPF), developed using chemical process simulator software and its validation was presented. The current paper focuses on optimizing the major output parameter of significant importance (namely higher heating value of syngas) with respect to the main operating parameters temperature, equivalence ratio (ER), and moisture content. The response surface method (RSM) is used to generate a mathematical relation between the response of interest which is heating value of syngas. The method was used to further determine the optimum conditions that lead to a higher heating value of syngas. The optimum values identified by RSM were; oxidation zone temperature of 1000oC, moisture content in the range of 4% and equivalence ratio of 0.35. These optimum operating condition values and the corresponding higher heating value of syngas was found to be in agreement with experimental results.